Principle of strict compliance in letter of credit: a comparative study from legal and Shariah perspective - Othman, Ahmad Azam; Che Hashim, Rosmawani (2012)
Letter of credit (LC) is a payment mechanism which is used to facilitate trade. One of the fundamental principles that govern the LC operation is principle of strict compliance. This principle indicates that in order to be paid; seller’s documents must strictly comply with the LCs’ requirement. This practice seems peculiar to the inherent nature of the contract of sale where the goods are customarily considered to be the only “factor” in making a payment. On the other hand, in LC transaction, banks are confined to handling financial and papers only, as provided by the UCP, “Bank deals with documents only”. Accordingly, payment for the goods is not honored upon compliance of the goods sold but it is paid on compliance of seller’s documents. Likewise, it is established that commercial banks worldwide, including Malaysian banks, adopt the same approach in dealing with documents in Islamic LC. The aim of this paper is to look at this practice which is originally conventional, from Shariah’s perspective. In order to determine the permissibility of stipulating such condition (a condition that payment in LC is honoured only upon compliance of documents) from Shariah’s point of view, it is imperative to study the position of Islamic law relating to freedom of stipulating condition in sale contracts. Among other things, this paper discusses the origin of the principle of strict compliance in LC transactions and the rationale of its application. Furthermore, it highlights Shariah issues in the principle of strict compliance in LC. Last but not least, it focuses on the views of the Muslim jurists in the issue of freedom of stipulating condition in sales contract. It is only by looking into the basic principles highlighted by the Muslim jurists on this issue; the permissibility of strict compliance principle can be ascertained.